Effect of asymptomatic bacteriuria on pregnancy outcome: a review - Neelima, Nalam; Gopalan, Ushadevi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Asymptomatic bacteriuria is more common in pregnancy and if left untreated it may progress to upper urinary tract infection. Early detection and treatment of asymptomatic bacteriuria prevents further progression of the infection and thereby preventing undesirable complications to the mother and fetus. It is advisable to do Urine culture and sensitivity in all antenatal women irrespective of the gestational age and symptoms.